2021
DOI: 10.3389/fcell.2021.684885
|View full text |Cite
|
Sign up to set email alerts
|

CUL5–ASB6 Complex Promotes p62/SQSTM1 Ubiquitination and Degradation to Regulate Cell Proliferation and Autophagy

Abstract: p62/SQSTM1 (sequestosome-1) is a key protein involved in multiple cellular bioprocesses including autophagy, nutrient sensing, cell growth, cell death, and survival. Therefore, it is implicated in human diseases such as obesity and cancer. Here, we show that the CUL5–ASB6 complex is a ubiquitin E3 ligase complex mediating p62 ubiquitination and degradation. Depletion of CUL5 or ASB6 induced p62 accumulation, and overexpression of ASB6 promoted ubiquitination and degradation of p62. Functionally, ASB6 overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Moreover, an increasing number of studies have suggested that SGK1 can regulate the functions of immune cells including T helper cells, and regulatory T cells in the tumor microenvironment ( Sang et al, 2020 ). SQSTM1 (better known as p62), is an autophagy receptor, and its activity mediates multiple biological functions including autophagy, cell growth, and cell death ( Gong et al, 2021 ). Recent studies have demonstrated that SQSTM1 promotes cell growth and induces autophagy in thyroid cancer by modulating AKT/mTOR signaling pathway ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an increasing number of studies have suggested that SGK1 can regulate the functions of immune cells including T helper cells, and regulatory T cells in the tumor microenvironment ( Sang et al, 2020 ). SQSTM1 (better known as p62), is an autophagy receptor, and its activity mediates multiple biological functions including autophagy, cell growth, and cell death ( Gong et al, 2021 ). Recent studies have demonstrated that SQSTM1 promotes cell growth and induces autophagy in thyroid cancer by modulating AKT/mTOR signaling pathway ( Yu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies have shown elevated (53), reduced (54,55) or unchanged (27,56) p62 muscle levels promoted by RT. That controversy may be explained due to the multifunctional role of p62, protein involved in many signal transduction pathways, including nutrition sensing (via mTORC1), inflammation and apoptosis (via NF-kB), antioxidant response (via Nrf2) (57), in addition to autophagy regulation. In fact, studies have demonstrated p62 and Nrf2 are essential for exercise-mediated enhancement of antioxidant protein expression in skeletal muscle (58).…”
Section: Discussionmentioning
confidence: 99%
“…Te ASB6 gene is a novel biomarker and potential therapeutic target in developing oral squamous cell carcinoma, hepatocellular carcinoma, breast cancer, and other tumors. Te ASB6 gene is a risk gene in tumors, and overexpression in various tumors can reduce endoplasmic reticulum stress response, promote flopodia formation, unsuppressed tumor growth, increase metastasis of cancer cells, and poorer patient prognosis [29][30][31][32]. A study confrmed that overexpression of the ASB8 gene in lung cancer has a regulatory efect on tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%